José Olallo Valdés: a Cuban male nurse to be remembered - Onassys Barreiro Alberdi; Yanet Blanco Fleites (Medisur)
José Olallo was a monk of the Order San Juan de Dios, who assumed infirmary practice as his profession, with a considerable humanist approach. He was a missionary who devoted his life to relief other people´s pain, no matter their religion, race, or social status, with no material profits for himself. This monk never studied nursery, but got his knowledge from the daily practice at the hospital of San Juan de Dios in Puerto Príncipe. He is an example for all those persons who choose this profession, for his perseverance, devotion and love. On November, 29th the Catholic Church beatified him in Camagüey city. He belonged to the order San Juan de Dios, founded by a Portuguese religious man in 1539.